"'WE' AND 'THEY'": WHY MUST WE ENGAGE IN CROSS‐CULTURAL CONVERSATION?: with Anindita N. Balslev, ""'We' and 'They'": Why Must We Engage in Cross‐Cultural Conversation?"; Carolyn J. Love, "Complex Identity: Genes to God"; Andrew B. Newberg, "Identity and the Brain: The Biological Basis of Our Self"; and John Calvin Chatlos, "Adolescent Identity Formation versus Spiritual Transformation.". Issue 1 (19th December 2022) - Balslev, Anindita N.
Abstract: This article contains the principal ideas that I presented in four different sessions at the IRAS 2022 conference, on the theme "'We' and 'They': Cross‐Cultural Conversation on Identity." Focusing on the central topic, the article begins with (i) the contents of my opening lecture; followed by (ii) a broad outline of the concerns discussed in my book, Cross‐Cultural Conversation: A New Way of Learning, intertwined with glimpses of the intellectual journey that led me to CCC, delivered in the Book‐discussion session; (iii) a summary of the main ideas about the importance of meeting of religions today, which formed the background for the CCC Panel discussion on religion, where I was in conversation with spokespersons of five world religions; and (iv) my comments on how science–religion dialogue can help promote a sense for human solidarity by combining knowledge with wisdom, in the concluding session.